Peran Lembaga Zakat Dompet Dhuafa Dalam Meningkatkan Perekonomian Kaum Dhuafa di Kota Medan - Annisa Aprilia; Zuhrinal M. Nawawi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2022)
Through their field work program, namely consumptive zakat and productive zakat, the Dompet Dhuafa zakat institution distributes and distributes zakat for cash assistance, infaq, and alms. Consumptive zakat is channeled through zakat funds, which are used for educational, humanitarian, social, and health projects. Productive Zakat Money works in the field of economic utilization work programs, making good use of these funds by employing people who have talent but lack capital. The farmer partner program formed by the Dompet Dhuafa zakat institution is one type of productive zakat distributed by Dompet Dhuafa. Siraman village is located in the Pekalongan area. by having two fostered hamlets, each of which has potential but lacks the infrastructure necessary to develop. The purpose of the study was to examine the function of the Dompet Dhuafa zakat institution in strengthening the economy of the poor in Medan City. Keywords: Dompet Dhuafa, Economic Improvement, and Islamic Economic Perspective